Development and characterization of antimicrobial films from gums obtained from cold-pressed flaxseed oil by-product - Kopuz, Seyma; Akman, Perihan Kubra; Tekin-Cakmak, Zeynep Hazal; Karasu, Salih (SPRINGER, 2024)
In this study, antimicrobial edible films incorporated with allyl isothiocyanate in free form (FG-EO) and nanoemulsion form (FG-NE) were produced using the gum obtained from a cold-pressed flaxseed oil by-product (FG). All films were characterized in terms of physicochemical, barrier, mechanical, biodegradability, thermal, and molecular properties. The results showed that integrating allyl isothiocyanate into the films improved the thermal and barrier properties of the films and decreased the tensile strength. According to the molecular characterization, the allyl isothiocyanate antimicrobial compound showed a homogeneous distribution in the film. The FG-EO films and FG-NE films provided strong antimicrobial effect against Escherichia coli O157:H7, Salmonella spp., Listeria monocytogenes, and Staphylococcus aureus pathogenic bacteria at rates ranging from 42 to 87%. Furthermore, during 15-day storage period of fresh-cut meat samples which were packaged with FG-Control, FG-EO, and FG-NE films, significant (P < 0.05) decrease in the number of total mesophile bacteria (TMB), total psychrophile bacteria, and coliform bacteria compared to control fresh-cut meat samples was observed. As a result, it could be said that allyl isothiocyanate incorporated FG-based edible films have the potential as an alternative packaging material to improve the quality of foods and extend the shelf life of fresh-cut meat.
Keywords: Antimicrobial film; Cold press linen oil by-product; Gum; Edible film; CINNAMON ESSENTIAL OIL; EDIBLE FILMS; PHYSICAL-PROPERTIES; PHYSICOCHEMICAL CHARACTERIZATION; RHEOLOGICAL PROPERTIES; MECHANICAL-PROPERTIES; NANOCOMPOSITE FILMS; COMPOSITE FILMS; ANTIOXIDANT; ANTIBACTERIAL; Polymer Science